Disability in emergency: An approach to the measures adopted by the Peruvian State in front of the pandemic - Noles Cotito, Mariela (2020)
As SARS-CoV-2 expanded throughout the world and became a pandemic, the idea of said virus as a “great equalizer” became popular due to its seemingly unrestricted transmission potential. However, this notion was promptly abandoned when it became clear that, despite everyone being at risk of contracting the virus, those most vulnerable are particularly defenseless and disproportionally impacted by it. On the one hand, the effects of the pandemic are exacerbated by the preexisting social and economic inequalities found in our society; conversely, the country’s own legal framework has rendered them unprotected. Among these, people with disabilities are a significant group. Representing almost 10% of the total population, they haven’t been subject of sufficiently effective and differentiated public policies to ensure their full inclusion and enjoyment of rights; situation that has gotten worst in the current health crisis. In this article we will explore the sociopolitical traits of citizens with severe physical disabilities in the country and how certain regulations issued by the government in the context of the pandemic have placed them in an increased vulnerable situation. Likewise, we will reimagine the new post-pandemic normality from the perspective of disability.